Sistem Informasi Pengarsipan Surat Masuk dan Surat Keluar Pada Dinas Tenaga Kerja dan Transmigrasi Kabupaten Musi Banyuasin - Rahayu Amalia; Nurul Huda (STMIK Budi Darma, 2020)
In an agency or company a letter is one of the most important communication media. The letter is in the form of incoming and outgoing letters. At the Banyuasin Regency Manpower and Transmigration Office, management of incoming and outgoing letters is still done manually starting from making, storing, documenting, to verifying letters, all done manually so as to result in ineffective and inefficient energy, time and cost. Letter Filing Information System can be a solution to this problem. The methodology used to design this information system is to use the RAD (Rapid Application Development) method and the program produced in this system is the Information System for Filing Incoming and Outgoing Letters at the Manpower and Transmigration Office of Musi Banyuasin Regency using PHP as a programming language and MySQL as the database